(untitled) (ENTHYMEMA, 2022)
Among the forms of hybridization characterizing the literature of twentieth century, the representation of museum in narrative texts creates different thematic and rhetorical declinations, and therefore lends itself to being analyzed though multiple hermeneutic perspectives. Configuring itself as a setting space of the plot, a literary transfiguration of real museums, or as a systematic collection of objects – collections sometimes taking on a metatextual value – the museum device interacts with the narrative writing and outlines a field still not too much explored by critical studies. Starting from these premises, the contribution intends to propose a reading of some of contemporary occurrences of the theme, both Italian and foreign, in particular in the texts La casa della vita (1958) by Mario Praz, The museum of innocence (2008) by Orhan Pamuk and, to guide the final considerations, Non luogo a procedere (2015) by Claudio Magris.